Office 365 administration (exam 70-346) - Kennedy, Norm; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"This course is designed to give users a tour and understanding of the administrative capabilities in Office 365. In this course, we will cover the Office 365 interface, setting up a trial of Office 365, navigating the Admin Center, adding and managing users, working with groups and collaboration groups, using group administration, and various other topics related to Office 365 administration. Additionally, understanding Azure rights management, deployment of Office 365 Pro Plus, monitoring of Office 365, creating custom domains, Hybrid Active Directory, Exchange administration, managing SharePoint Online, configuring Skype for Business and performing connectivity tests will be covered."--Resource description page.
Title from resource description page (Safari, viewed September 13, 2016).
Presenter, Norm Kennedy.
Keywords: Microsoft Office; Business -- Computer programs; Electronic books